TINGKAT ASUPAN PROTEIN, VITAMIN A, DAN ZINK YANG RENDAH MEMPERLAMA KESAKITAN ISPA PADA BALITA DENGAN ISPA - Agnes Nihi Leo (Jurnal Pangan dan Gizi, 2018)
Result of Basic Healt Research in 2013 showed NTT as province with highest incidence of URI reached 41,7% above national prevalence (25%) and higest characteristic people with URI are toddler. The with long of URI’s morbidity in toddler. The study is cross sectional design. Number of subject is study aimed to analyze correlation of nutrient intake level, nutritional statues, and history of exclusive breastfeeding 87 subjects that selected with purposive sampling. Correlation analysis by spearman test with 95% confidence interval. The result showed there are correlation of protein intake level, Zn intake, and vitamin A intake with long of URI’s morbidity, while nutritional status and history of exclusive breastfeeding are not correlation wot long of URI’s morbidity. Suggest to increase protein, Zn, and vitamin A intake to shorted morbidity of URI.